What's the worst that could happen? existential risk and extreme politics - Leigh, Andrew 1972- (The MIT Press, 2021)
"An analysis of the ways in which populist politics place our long-term well-being at risk, exploring pandemics, climate change, nuclear war and other issues"--
Keywords: Demokratie; Radikalismus; Politik; Populismus; Populism; Radicalism; Democracy; Existentialism; POLITICAL SCIENCE / General